Nuclear-localized SIRT1 inhibits apoptosis via deacetylating p53 - Cheng, Lin; Wu, Ge; Yao, Wei; Deng, Kangrong; Zhang, Chunsun; Chen, Tongsheng (The international journal of biochemistry & cell biology, 2025)
The function of silencing information regulator 1 (SIRT1) in promoting or inhibiting apoptosis remains a subject of debate. Here, we aim to evaluate the roles of nuclear-localized SIRT1 in STS/DOX-induced apoptosis. Silencing nuclear-localized SIRT1 significantly enhanced STS/DOX-induced apoptosis, while overexpression of nuclear-localized SIRT1 markedly inhibited STS/DOX-induced process, demonstrating the anti-apoptotic ability of the nuclear-localized SIRT1. Critically, silencing p53 compromised the anti-apoptotic function of nuclear-localized SIRT1, thereby underscoring the essential role of p53 in mediating SIRT1's anti-apoptotic capability. Western blot analysis further revealed that wild-type SIRT1 robustly downregulated Ac-p53 expression to inhibit apoptosis, whereas a deacetylase-defective mutant of SIRT1 (SIRT1H363Y) markedly upregulated Ac-p53 to promote apoptosis. Fluorescence resonance energy transfer (FRET) analyses for the cells co-expressing nuclear-localized SIRT1-CFP and p53-YFP showed that STS enhanced the direct interaction between SIRT1 and p53 in nucleus, suggesting that the nuclear-localized SIRT1 directly interacts with p53 to deacetylate p53, thus inhibiting apoptosis. On the contrary，overexpression of cytoplasm-localized SIRT1 markedly promoted STS/DOX-induced apoptosis, firmly demonstrating the pro-apoptotic ability of the cytoplasm-localized SIRT1. These results firmly demonstrate a notion that nuclear-localized SIRT1 inhibits apoptosis via deacetylating p53.